Analisis Kualitatif Dan Kuantitatif Dokumen Rekam Medis Rawat Inap Sectio Caesarea: Literature Review - Resta Dwi Yuliani (Jurnal Rekam Medis & Manajemen Infomasi Kesehatan, 2023)
Based on the 2018 Riskesdas data, it is stated that delivery is by means of action cesarean sectionreached 17.6%. This event is considered to exceed the standards set by WHO. The purpose of this study was to analyze qualitative and quantitative inpatient medical record documents cesarean section with review literature. The results of this study were based on a qualitative analysis of medical record documents on the 4 articles that were conductedreviews, based on qualitative analysis seen from a review of the completeness and consistency of diagnoses,reviews completeness and consistency of diagnostic records, reviews recording during care and treatment,reviews exists informed consent there are still many medical record documents that are not complete and consistent, one of the factors that influence this incompleteness is the level of awareness of health service workers who lack the importance of completing patient medical record documents. Meanwhile, based on quantitative analysis, from the 4 articles inreviewsthere is only 1 article that states its completeness reaches 100%. Reviews identification of incompleteness on the sex item, reviews authentication is found in the nurse's signature and full name, doctor's name and signature, reviewsreporting of incomplete filling in filling out the main and entry diagnoses and not attaching the results of laboratory examinations, where as on reviews records are in illegible writing in the case of doctors' and nurses' writings that are unclear or illegible, corrections in writing strokes that are not signed. Keywords: qualitative analysis, quantitative analysis, sectio caesarea.